تأثیر خودگویی ارگانیک بر فراشناخت و عملکرد در تکلیف وامانده ساز. - جهانگیر خورشیدی; امیر دانا (Shenakht Journal of Psychology & Psychiatry, 2025)
Introduction: Goal-directed self-talk, as a form of organic self-talk, serves as a supportive mechanism for the development of various psychological, leadership, relaxation, and concentration skills. It employs self-regulatory strategies to prevent or address psychological challenges. Aim: The aim of the present study was to study the effect of organic self-talk on metacognition and performance in Exhausting task. Method: This study employed a quasi-experimental design, involving 48 voluntary participants selected from physical education students. The participants were randomly assigned to either a selftalk intervention group or a control group. Initially, a pre-test was conducted to assess participants' performance in an exhaustive task using the Bruce test, as well as their metacognitive abilities using the Metacognition and Metaemotion Questionnaire for Athletes. Subsequently, a Goal-Directed SelfTalk protocol was developed based on psychological challenges encountered in endurance tasks and delivered to the self-talk group across three training sessions. Following the intervention, a post-test was administered to measure the same variables assessed at baseline. Data were analyzed using analysis of covariance (ANCOVA) at the 0.05 significance level in SPSS. Findings: The results of ANCOVA indicated that goal-directed self-talk significantly enhanced performance in the exhaustive task (F (1, 45)=61/5, p>0/001). Additionally, the intervention led to a notable increase in participants' metacognitive thinking (F (1, 45)=27/2, p>0/001). Conclusion: Overall, goal-directed self-talk facilitated athletes' adaptation to psychological challenges encountered during the exhaustive task by enhancing their self-awareness. Consequently, it may serve as an effective intervention for improving endurance performance.